PERLINDUNGAN HUKUM TERHADAP PELAKU TINDAK PIDANA PENCUCIAN UANG PASIF YANG MEMILIKI ITIKAD BAIK UNTUK MEWUJUDKAN KEPASTIAN HUKUM - Mochamad Luthfi Zulfikar; Kristiawanto Kristiawanto; Marsudin Nainggolan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to analyze the legal regulation of passive money laundering perpetrators who have good intentions based on positive law in Indonesia and analyze the form of legal protection for passive money laundering perpetrators who have good intentions to realize legal certainty. The issues raised focus on how to regulate passive money laundering perpetrators who have good intentions based on positive law in Indonesia and what form of legal protection for passive money laundering perpetrators who have good intentions to realize legal certainty. The research method used is normative legal research with a statute approach, a conceptual approach, a case approach, and a comparative approach. Data sources are obtained from primary legal materials in the form of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945), the Criminal Code (KUHP), Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes, Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2013 concerning Procedures for Settling Applications for Handling Assets in Money Laundering Crimes or Other Crimes, Government regulations or other implementing regulations. The research findings implementation of passive money laundering perpetrators who have good intentions has adopted a broad approach to encompassing passive perpetrators to enhance the effectiveness of crime eradication. However, this expansion still leaves legal issues, particularly regarding the unclear parameters of the phrase